VD_FINDINFO Jug / 2017 / 109 vom 15. Juni 2016 - VD Tribunal cantonal (2016)
FIXATION DE LA PEINE, PEINE D'ENSEMBLE, TRAITEMENT AMBULATOIRE, TOXICOMANIE | 110 ch. 7 CP, 46 al. 1 CP, 49 CP, 51 CP, 60 CP, 63 al. 1 CP